Effects of Rh-Negative Blood Group on Pure Tone Thresholds and Immittance Test Results - Kamalakannan Karupaiah; Sundaresan Ramachandran; Delna Saji; Jerlin Xavier; Ann Rose Chiyezhan; Nilesh Jeevandas Washnik; Prashanth Prabhu (Auditory and Vestibular Research)
Background and Aim: Human blood group system variations may impact the individual’s health and hearing status. It was found that individuals with O-positive blood are more prone to noise-induced hearing loss, and they exhibit reduced amplitude in otoacoustic emissions, elevated Acoustic Reflex Threshold (ART), and a slightly higher resonance frequency of the middle ear. Hence, a study was needed to observe if the same trend is followed for those with Rh-ve blood groups. Methods: A cross-sectional group post-test-only design with a non-random convenient sample was applied. This study was conducted with forty adult female participants with a pure tone threshold range of less than or equal to 15 dBHL and ages ranging from 18 to 25 years. In each blood group (A–, B–, O–, AB–), 10 participants were recruited. All participants underwent immittance evaluation, pure tone audiometry, and extended highfrequency audiometry. Results: On analyzing the data, participants with the O negative blood group showed significantly elevated ART in both ipsilateral and contralateral ears. Also, there was no significant difference for pure tone thresholds for the frequencies 250 Hz to 16 kHz and tympanometry findings. Conclusion: This study indicates that the elevated ARTs in O negative blood group people could be attributed to relatively increased stiffness in the middle ear and fewer outer hair cells compared with other blood groups.